2007
DOI: 10.1093/aob/mcm251
|View full text |Cite
|
Sign up to set email alerts
|

Determinate Root Growth and Meristem Maintenance in Angiosperms

Abstract: This review considers the mechanisms of determinate root growth to better understand how the RAM is maintained, how it functions, and the cellular and genetic bases of these processes. The role of the quiescent centre in RAM maintenance and exhaustion will be analysed. During root ageing, the RAM becomes smaller and its organization changes; however, it remains unknown whether every root is truly determinate in the sense that its RAM becomes exhausted before senescence. We define two types of determinate growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 164 publications
3
61
1
5
Order By: Relevance
“…8a) also demonstrated clearly that differentiation of xylem reaches to within a few millimetres of the root tip of the dormant roots once its apex ceases growth and cell division. These developmental events in roots, where growth is temporarily or permanently suspended, are well illustrated in the literature (McCully, 1999;Shishkova et al, 2008).…”
Section: Implications Of Contrasting Xylem Maturation Along Shallow Rmentioning
confidence: 87%
“…8a) also demonstrated clearly that differentiation of xylem reaches to within a few millimetres of the root tip of the dormant roots once its apex ceases growth and cell division. These developmental events in roots, where growth is temporarily or permanently suspended, are well illustrated in the literature (McCully, 1999;Shishkova et al, 2008).…”
Section: Implications Of Contrasting Xylem Maturation Along Shallow Rmentioning
confidence: 87%
“…The extent to which the primary growth of fine roots in trees is indeterminate (or not) remains unknown (Shishkova et al 2008). However, minirhizotron studies have demonstrated clearly that growth and mortality may occur simultaneously in the root system.…”
Section: The Phenology Of Fine Rootsmentioning
confidence: 99%
“…The maintenance of RAM and its organization during indeterminate growth requires a highly orchestrated balance between the production of new cells in the RAM and the rate of their displacement towards the elongation zone (Ivanov 1974(Ivanov , 1994Barlow 1976). The transition to elongation is related to the duration of a cell cycle and to the number of division cycles that meristematic cells pass while in the RAM (Ivanov 1974(Ivanov , 1994Shishkova et al 2008). A very peculiar feature of mko1 mutant is that no clear transition to rapid elongation could be found.…”
Section: Identification Of the Moots Koom 1 (Mko1) Arabidopsis Thaliamentioning
confidence: 99%
“…Tight regulation of cell production in the root apical meristem (RAM) is indispensable for meristem maintenance and for subsequent transition of meristematic cells to elongation and differentiation. A plant organ has indeterminate growth when it has a functional meristem, either active or with the potential to resume its activity (Shishkova et al 2008). The indeterminate growth of Arabidopsis thaliana (Arabidopsis) roots represents an interesting developmental model in which a complex network of genetic programs interact to establish and maintain stereotypic patterns of cell proliferation, cell growth, and cell identities.…”
Section: Introductionmentioning
confidence: 99%